Analisis Kadar Timbal Pada Kosmetik Lipcream Yang Beredar Di Pasar Batu Aji Kota Batam - Sammulia, Suci Fitriani; Utami, Rury Trisa; Hana Salsabila Wulandari (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2024)
Lip cream cosmetics are widely used by the public, but they potentially contain heavy metals such as lead (Pb), which are toxic. This study aims to determine the presence and levels of lead in lip cream cosmetics sold at Batu Aji Market, Batam City. This study was a laboratory experiment using a qualitative test method using Potassium Iodide (KI) solution and a quantitative test using UV-Vis spectrophotometry. Five lip cream samples without BPOM notification numbers were selected through purposive sampling. The test results showed that all samples were negative for lead, indicated by the absence of a yellowish-white precipitate and the absence of a typical lead absorption peak at a wavelength of 426 nm. Thus, all samples met the maximum limit for lead heavy metal contamination set by BPOM (≤20 mg/kg). Routine monitoring of heavy metal content in cosmetics remains necessary to ensure product safety on the market